2022
DOI: 10.3390/molecules27154719
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Reactions and Their Biological Contributions in Honey

Abstract: Honey is known for its content of biomolecules, such as enzymes. The enzymes of honey originate from bees, plant nectars, secretions or excretions of plant-sucking insects, or from microorganisms such as yeasts. Honey can be characterized by enzyme-catalyzed and non-enzymatic reactions. Notable examples of enzyme-catalyzed reactions are the production of hydrogen peroxide through glucose oxidase activity and the conversion of hydrogen peroxide to water and oxygen by catalase enzymes. Production of hydroxymethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 105 publications
0
18
0
1
Order By: Relevance
“…Interestingly, enzymatic activity in the honey also differed, with a notably lower invertase in clover compared to the other varietals. Enzymes such as catalase, diastase, and invertase can liberate glucose and fructose from oligosaccharides and disaccharides found within honey (24). Honey ripening has been correlated with the invertase activity and sucrose concentration, and low levels of invertase activity indicate honey quality (25).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, enzymatic activity in the honey also differed, with a notably lower invertase in clover compared to the other varietals. Enzymes such as catalase, diastase, and invertase can liberate glucose and fructose from oligosaccharides and disaccharides found within honey (24). Honey ripening has been correlated with the invertase activity and sucrose concentration, and low levels of invertase activity indicate honey quality (25).…”
Section: Discussionmentioning
confidence: 99%
“…Honey ripening has been correlated with the invertase activity and sucrose concentration, and low levels of invertase activity indicate honey quality (25). Glucose oxidase also has the capacity to convert glucose into hydrogen peroxide, an enzyme that was significantly lower in both clover and orange, a compound that is associated with antimicrobial function (24). Our results revealed that clover honey enhanced probiotic survivability through an in vitro digestion system compared to the other honey varietals (alfalfa, buckwheat, and orange blossom) and controls.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the invertase enzyme is responsible for breaking down sucrose in honey into glucose and fructose. In contrast, the diastase enzyme is responsible for the conversion of polysaccharides (e.g., amylose) to glucose (Mohammed et al., 2022). Although invertase and diastase enzymes are produced by honeybees, they can be used as a parameter to determine the botanical origin of plants.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…25 Antibacterial activity: Direct exposure of honey against microorganisms has multifactorial actions as, physically (free acidity 26 and hyper osmolarity since microorganisms can't survive and grow in the hypertonic sugar solution or in low pH medium). 27 Biochemically, enzymatic system (catalase, glucose oxidase and peroxidase 28 that produces continuous hydrogen per oxide 12 by glucose oxidase, an enzyme derived from the honeybee 29 and other enzymes; β-glucosidase, α/β-amylase, maltase, esterase, etc.. 30 As well as various biochemical nonenzymatic substances potent biological micro components mainly flavonoids and phenolic compounds. 31 Different flavonoids (kaempferol, quercetin, pinobanksin, chrysin, galangin, pinocembrin 32 with different antimicrobial mechanisms such as inhibition of nucleic acid synthesis 33 inhibition of cytoplasmic membrane function, inhibition of energy metabolism, inhibition of the attachment and biofilm formation, 34 inhibition of the porin on the cell membrane, alteration of the membrane permeability, and attenuation of the pathogenicity.…”
Section: Introductionmentioning
confidence: 99%
“…31 The hydroxyl and superoxide free radicals contribute to the antibacterial activity of honey due to powerful damaging effect on the bacterial cells and DNA. 30 Flavonoids and phenolic acids (derived from plant origin) are highly bioactive particles and present great molecular diversity, but phenolics (phenolic acids, flavonoids) are the most abundant and have the highest antiradical activity. 35 Honey 36 and propolis 37 stimulated ROS generation, TLR-2 and TLR-4 expression and the production of proinflammatory cytokines by murine macrophage and enhanced its bactericidal activity.…”
Section: Introductionmentioning
confidence: 99%